Development of novel sulfur/carbon cathode composites using spray pyrolysis and study of their electrochemical performance in lithium-sulfur batteries - Umirov, N.; Yesibolati, N.; Batyrbekuly, D.; Mentbayeva, A.; Sugurbekov, E.; Konarov, A.; Kurmanbayeva, I.; Hara, Toru; Bakenov, Zhumabay (Nazarbayev University, 2014)
The eminent global energy crisis and growing ecological concerns in the past two decades have led to intensive development in the fields of green transportation such as electric and hybrid electric vehicles (HEV), as well as clean energy sources such as wind and solar power. These technologies demand low cost, safe, and environmentally friendly energy storage systems. Therefore, development of novel economically feasible and ecologically friendly high performance batteries is crucial. Lithium/ sulfur (Li/S) batteries have the highest energy density (2600 Wh/kg) and theoretical capacity (1672 mAh/g) among all known systems [1,2].
Keywords: ecological; energy; sulfur; carbon; electrochemical; spray pyrolysis; cathode